HAK PEREMPUAN DALAM PENGASUHAN ANAK PASCA PERCERAIAN - Aris Aris; Fikri Fikri (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
Hadanah or parenting is something that can not be released in the context of marriage or family law of Islam. This paper discusses the care of children in the perspective of Islamic law. Parenting in marriage is not much of a problem and does not give rise to detailed rules, but parenting with divorced parents is arranged in detail. The conclusion of Islamic jurist shows that the woman or the mother is more entitled to the child to do hadanah.Hak women are associated with the child's age and the nature and character of parents.